Feasibility Study of Expanded Clay Aggregate Lightweight Concrete for Nonstructural Applications - Shayan Ali Khan; Fazal Hussain; Rao Arsalan Khushnood; Hassan Amjad; Farhan Ahmad (Advances in Civil Engineering)
In nonstructural infill panels, common materials like expanded polystyrene panels face fire susceptibility, autoclaved aerated concrete (AAC) incurs high production costs, and traditional bricks come with a significant carbon footprint and weight. So, there is a requirement for infill panels that are not just resilient and lightweight but sustainable as well. This study seeks to address these issues by introducing sustainable and lightweight expanded clay aggregate (ECA) in concrete. Firstly, eight ECA mix designs were prepared by integrating fly ash and kerosene with clay, and ECA with a bulk density of 0.59 g/cm³ and compressive strength of up to 1.73 MPa were prepared. The lightest ECA mix was then chosen to explore their use in lightweight aggregate concrete (LWAC) along with fly ash as a secondary cementitious material. The resulting LWAC had a minimum density of 1,050 kg/m³ and a compressive strength of 6.8 MPa, fulfilling the standard requirements of a minimum of 3.5 MPa for nonstructural concrete.